Pengembangan media pembelajaran berbasis e-flipbook melalui canva pada materi satuan waktu untuk peserta didik kelas III sekolah dasar - Hapsari, Happy Tias; Riyadi, Riyadi; Budiharto, Tri (Didaktika Dwija Indria, 2023)
Learning media is an intermediary in learning to make it easier for teachers to convey material to students. This study aims to determine the process and results of developing e-flipbook based learning media through Canva that are valid and practical. This study uses the Research and Development (RnD) development research method through the Borg and Gall model modified by Sukmadinata which includes 3 stages, namely preliminary study, model development and model testing. This research is limited to the development stage. The data analysis technique used is descriptive qualitative. Research instruments in the form of observation, interviews, documentation studies, and questionnaires. The results of the research produced valid learning media because it obtained an assessment from material experts of 86.52% and an assessment of media experts of 85.5%. And produce learning media that is practical because it gets an assessment from students with a result of 95.66%. The theoretical implication of this research is that learning media is declared valid and can be used as a reference in further learning and research. The practical implication is that the media is presented in the form of an interesting digital book with the addition of quizzes, pictures, learning videos and evaluation questions.